If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -9 = -5x + 11 Reorder the terms: -9 + -3x = -5x + 11 Reorder the terms: -9 + -3x = 11 + -5x Solving -9 + -3x = 11 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -9 + -3x + 5x = 11 + -5x + 5x Combine like terms: -3x + 5x = 2x -9 + 2x = 11 + -5x + 5x Combine like terms: -5x + 5x = 0 -9 + 2x = 11 + 0 -9 + 2x = 11 Add '9' to each side of the equation. -9 + 9 + 2x = 11 + 9 Combine like terms: -9 + 9 = 0 0 + 2x = 11 + 9 2x = 11 + 9 Combine like terms: 11 + 9 = 20 2x = 20 Divide each side by '2'. x = 10 Simplifying x = 10
| -10+6x=5x+8 | | -2(-2x+3)=-5(x+8) | | 8x-9y=45 | | 4=-1-2(2p+3) | | 7-p=-1 | | y=x^2-6x+3 | | 4x^2+9y^2= | | 3+3=n | | 1/2=19+22 | | -.5x*-7=-11 | | 9m+11=2 | | 27+2x=13 | | 12x^2=27 | | 4x-17=x+13 | | 2c-31=-9c+24 | | 5w-5=12w | | 27-2x=13 | | -4y=6y | | 19=1/2+22 | | -27-2c=7c | | y=2x^2+16x+8 | | 5x=-6x-77 | | 8-3x-5=2x-12 | | 7(4-2x)-6=-12 | | 9.36k-2.021=9.89k | | 0=1/2(20+16) | | 4x-9=x+15 | | 3x+1=x+21 | | x^2-10x+25=12 | | 8x^2+90x-225=0 | | 5y+4=2y | | 13=1/2(4x-10+3x+8) |